FAMILIAL DYSBETALIPOPROTEINEMIA (TYPE III HYPERLIPOPROTEINEMIA) - P. P. Malyshev; A. V. Tyurina; T. A. Rozhkova; M. Y. Zubareva; V. A. Amelyushkina; Y. A. Shuvalova; D. V. Rebrikov; A. I. Kaminny (Евразийский Кардиологический Журнал, 2019)
The aim of this work was to describe a series of cases of familial dysbetalipoproteinaemia (FD) - a rare recessive disorder of lipid metabolism. The study included 18 patients of both sexes, mean age was 42.4 years. Quantitative determination of total cholesterol (TC) and triglycerides (TG) was carried out by a unified enzymatic method, high density lipoprotein (HDL) and low-density lipoprotein (LDL) - by a direct homogeneous method. The APOE gene rs7412 variant was determined by real-time polymerase chain reaction (PCR) using adjacent samples and by melting reaction products after PCR. The frequency of FD according to DNA analysis among 367 patients with different types of hyperlipidemia was 4.9%. CHD was detected in 27.8% of patients. Different types of xanthomas were detected in 22.2% of patients. When comparing the initial lipid profile of patients with FD and those in the control group, significantly higher levels of TC, TG, state Budget-funded Institution National Medical Research center of cardiology of the Ministry of Health of the Russian Federation LDL-C and non-HDL-C were observed, while plasma HDL-C levels were significantly lower than in the control group. On lipid-lowering therapy (statin and/or fibrate), the average levels of TC, TG and non-HDL cholesterol decreased approximately 2 times from baseline (p<0.002), and LDL decreased 1.5 times (p<0.008). The goal level of non-HDL-C among patients with high cardiovascular risk (<2.6 mmol/l) during therapy was not achieved in anyone, and high risk (<3.4 mmol/l) was achieved only in 2 of 5 patients. The data obtained show that, despite the favorable changes in the lipid profile, many patients with FD on current therapy remain untreated; therefore, to increase the effectiveness of therapy, it is necessary to increase the dose of statin (in the absence of contraindications) and/or combine statins with fibrates.